2005
DOI: 10.1111/j.1600-0633.2005.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Nested patterns of spatial diversity revealed for fish assemblages in a west European river

Abstract: Nested patterns of spatial diversity revealed for fish assemblages in a west European river Un resumen en españ ol se incluye detrás del texto principal de este artículo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 46 publications
1
34
0
2
Order By: Relevance
“…The pool of species colonizing a basin is then screened based on the local climate, considering the potential differences in temperature or water availability that is, at least in part, responsible for assemblage characteristics of the tributaries (Tonn, 1990;Jackson et al, 2001). Within a tributary, the species assemblage is then distributed according to the upstream-downstream gradient (Huet, 1959;Vannote et al, 1980;Ibarra et al, 2005;Ferreira and Petrere, 2009). Finally, at the local habitat scale, both physical habitat features and biotic interactions determine the fish assemblage that co-occurs at a particular place on the stream (Tonn, 1990;Jackson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The pool of species colonizing a basin is then screened based on the local climate, considering the potential differences in temperature or water availability that is, at least in part, responsible for assemblage characteristics of the tributaries (Tonn, 1990;Jackson et al, 2001). Within a tributary, the species assemblage is then distributed according to the upstream-downstream gradient (Huet, 1959;Vannote et al, 1980;Ibarra et al, 2005;Ferreira and Petrere, 2009). Finally, at the local habitat scale, both physical habitat features and biotic interactions determine the fish assemblage that co-occurs at a particular place on the stream (Tonn, 1990;Jackson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Faced with the widespread problem related to the difficulty of obtaining reliable and usable data sets, recent advances in conservation biology have suggested that presence-absence data are particularly suitable for the assessment of species distribution in a conservation context (MacKenzie, 2005;Vojta, 2005). Despite the simplicity of such input data, they can provide reliable information for analyzing species distribution, especially in a conservation context (Joseph et al, 2006), and above all the distributions of fish assemblages (Ibarra et al, 2005;Lasne et al, 2007aLasne et al, , 2007b, certain fish species (Oberdorff et al, 2001;Pont et al, 2005), migratory fishes (Eikaas and MacIntosh, 2006) and eel (Broad et al, 2001;. In fish, electrofishing methods are among the most common ways of sampling fish.…”
Section: > Assessing Distribution Patterns With Logistic Modelsmentioning
confidence: 99%
“…This distribution pattern does not completely match the models presented by Frič, Borne & Nowicky in the 19 th century (Holčík et al 1989) or with the model of Ibarra et al (2005). The distribution of Alpine bullhead, common minnow and European chub is similar to the models of Ibarra et al (2005) and Lasne et al (2007). Furthermore, two more species (spirlin and Carpathian barbel), seem to be the key species for the middle reaches of the Udava stream.…”
Section: Discussionmentioning
confidence: 60%